Toward an Intercultural Natural History of Brazil The Historia Naturalis Brasiliae Reconsidered - Françozo, Mariana (Routledge Studies in Global Latin America, 2023)
This volume presents the first extensive census of the surviving copies of the treatise Historia Naturalis Brasiliae in libraries worldwide and examines the book from a variety of interdisciplinary viewpoints. The chapters in this volume are written by scholars from different fields of knowledge, including anthropology, botany, linguistics, literature, book history, medieval and early modern history, and art history. The chapters contextualize the treatise vis-à-vis its predecessors and contemporaneous works of natural history and examine its botanical, zoological, and linguistic accuracy and usefulness in the present day. Put together, the seven chapters of this volume present a kaleidoscope of possibilities of how to re-interpret Piso and Marcgraf's work within the dynamic context of knowledge-production about the 'New' World in the early modern era, while also suggesting approaches to continue profiting from its subject matter in the present day. Toward an Intercultural Natural History of Brazil offers essential reading on the Historia Naturalis Brasiliae, natural history and Latin American history.